Mapping the Potential of Social Accounting Implementation in Indonesian Government: A Scoping Review - Firmansyah, Amrie (Universitas Muhammadiyah Yogyakarta, 2026)
Research aims: This study aims to map the potential implementation of social accounting in the Indonesian government by identifying and classifying existing public policies, national development frameworks, social indicators, budgeting instruments, and public accountability mechanisms that reflect social dimensions within the public sector. Design/Methodology/Approach: This study employs a scoping review, adhering to established principles. The analysis examines national development documents, social indicator systems, budgeting guidelines, public performance accountability regulations, and selected international governance and reporting standards relevant to social accountability in the public sector. Research findings: The findings show that social dimensions have been formally institutionalized within Indonesia's development planning, budgeting, performance measurement, and accountability systems. Social objectives, indicators, and outcomes are embedded in long-term and medium-term development plans, SDGs frameworks, gender-responsive budgeting guidelines, and public sector performance accountability regulations. However, these social elements remain fragmented across policy, performance, and governance instruments and have not yet been integrated into the government accounting system. This fragmentation indicates that the potential for social accounting development in Indonesia is primarily integrative rather than formative. Theoretical Contribution/Originality: This study makes a significant contribution to public sector accounting by extending the discourse on social accounting into the context of government institutions in Indonesia. It provides a systematic mapping of existing social accountability elements, positioning social accounting as a conceptual bridge between development policy frameworks and public sector accounting systems. Practitioner/Policy Implication: The findings provide policymakers with an evidence-based foundation for integrating existing social indicators and accountability mechanisms into a more comprehensive public-sector accounting framework, without requiring the creation of entirely new social measurement systems. Research limitation/Implication: This study does not assess the operational implementation or effectiveness of social accounting practices and is limited to document-based analysis.